Combating the 'myth of physical restraint' in human trafficking and modern slavery trials heard in the Crown Court. (January 2022) - Murphy, Jack
The greatest hurdle to an effective criminal justice response to human trafficking is the prevalence of myths about how exploitation happens and who 'counts' as a genuine victim. This includes the myth that, to be a genuine victim, an individual must have been subject to some form of physical restraint. Previous work has demonstrated how this myth undermines trafficking prosecutions in various jurisdictions. It has demonstrated that, in the absence of physical restraint during their exploitation, victims are deemed to lack credibility. However, what is missing in the current body literature is a robust analysis of whether something should be done to address this issue. By engaging with the foundational principle of accurate fact-finding, this article argues that some form of regulation of cross-examination in the English and Welsh jurisdiction, with a view to preventing this myth from manifesting in trials, would be justified.